Síndrome de Burnout y estrategias de afrontamiento en docentes de la Unidad Educativa Fernando Suárez Palacio, periodo 2021-2022 - Maza Veintimilla, Olivia Mariana (2022)
Burnout syndrome is a period of physical, emotional and mental tiredness, which manifests itself as a consequence of overwhelming demands, chronic stress or job dissatisfaction, disturbing the personality and self-esteem of those who suffer from it. As a remedy against this attrition the individual uses coping strategies, which avoid, diminish or solve problems at the individual or social level in order to recover or maintain the balance. The main objective of the present study was to establish the relationship between Burnout syndrome and coping strategies. The methodology used was exploratory, descriptive, correlative and transversal, in which 53 teachers from the Educational Unit Fernando Suarez Palacios participated. The instruments used were the Burnout Inventory of Maslach and the scale of CSI coping strategies in order to know the levels of each of the dimensions and the type of strategy used. Among the results it can be evidenced the absence of Burnout in the majority of the respondents and the most used strategy is the resolution of problems